Vasoactive-ventilation-renal score and outcomes in infants and children after cardiac surgery - Abhay, Pota; Sharma, Rajesh; Bhan, Anil; Raina, Manan; Vadhera, Ananya; Akole, Romel; Mir, Firdoos Ahmad; Bajpai, Pankaj; Misri, Amit; Srivastava, Swarnika; Prakash, Ved; Mondal, Tanmoy; et al. (Frontiers in Pediatrics, 2023)
Introduction: There is a need to index important clinical characteristics in pediatric cardiac surgery that can be obtained early in the postoperative period and accurately predict postoperative outcomes. Methodology: A prospective cohort study was conducted in pediatric cardiac ICU and ward on all children <18 years undergoing cardiac surgery for congenital heart disease from 9/2018-10/2020. Vasoactive-Ventilation-Renal (VVR) score was analyzed to predict outcomes of cardiac surgeries with comparison of post-operative variables. Results: A total of 199 children underwent cardiac surgery during the study period. The median (IQR) age was 2 (0.8-5) years and weight was 9.3 (6-16) kg. The most common diagnoses were ventricular sep¬tal defect (46.2%) and Tetralogy of Fallot (37.2%). At 48th hour, AUC (95% CI) values were higher for VVR score than other clinical scores measured. Similarly, at 48th hour, AUC (95% CI) values were higher for VVR score than other clinical scores measured for length of stay and mechanical ventilation. Discussion: The VVR score at 48 hours post-operation was found to best correlate with prolonged PICU stay, length of hospitalization and ventilation duration with the greatest AUC-ROC (0.715, 0.723, and 0.843, respectively). 48-hour VVR score correlates well with prolonged ICU, hospital stay and ventilation.